Verbal-analytical rather than visuo-spatial Raven's puzzle solving favors Raven's-like puzzle generation - Srivastava, Priyanka; Jaarsveld, Saskia; Sangani, Kishan (Frontiers in Psychology, 2023)
Raven’s advanced progressive matrices (APM) comprise two types of representational codes, namely visuo-spatial and verbal-analytical, that are used to solve APM puzzles. Studies using analytical, behavioral, and imaging methods have supported the multidimensional perspectives of APM puzzles. The visuo-spatial code is expected to recruit operations more responsive to the visual perception tasks. In contrast, the verbal-analytical code is expected to use operations more responsive to the logical reasoning task and may entail different cognitive strategies. Acknowledging different representational codes used in APM puzzle solving is critical for a better understanding of APM’s performance and their relationship with other tasks, especially creative reasoning. We used eye-tracking method to investigate the role of two representational codes, visuo-spatial and verbal-analytical, in strategies involved in solving APM puzzle and in generating an APM-like puzzle by using creative-reasoning task (CRT). Participants took longer time to complete the verbal-analytical than visuo-spatial puzzles. In addition, visuo-analytical than visual-spatial puzzles showed higher progressive and regressive saccade counts, suggesting the use of more response elimination than constructive matching strategies employed while solving verbal-analytical than visuo-spatial puzzles. We observed higher CRT scores when it followed verbal-analytical (Mdn=84) than visuo-spatial (Mdn=73) APM puzzles, suggesting puzzle-solving specific strategies affect puzzle-creating task performance. The advantage of verbal-analytical over visuo-spatial puzzle-solving has been discussed in light of shared cognitive processing between APM puzzle-solving and APM-like puzzle-creating task performance.